2020
DOI: 10.1016/j.ajodo.2019.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between normative and self-perceived criteria for orthodontic treatment need and satisfaction with esthetics and mastication in adolescents

Abstract: Introduction: Orthodontic treatments are performed to improve esthetics and masticatory functions. In general, clinical criteria are used to recommend such treatments without considering the opinion of the patient. This study aimed to evaluate the relationship between technically defined orthodontic need (normative criteria) and the need for treatment perceived by adolescent patients. Methods: A total of 215 students aged between 15 and 19 years were selected and asked to respond to a questionnaire concerning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
2
10
0
5
Order By: Relevance
“…Other studies have also confirmed that the concern of an individual with good appearance is generalized in any society. 24,25 Consistent with previous studies, 26,27 statistical associations were found between gender and impact on quality of life, with the girls presenting 2.54 times more chances of having an impact than boys. Girls, usually, are more sensitive to the perception of their own appearance than boys, 26,28 present more attention, perception and appreciation of with own oral health.…”
Section: Discussionsupporting
confidence: 86%
“…Other studies have also confirmed that the concern of an individual with good appearance is generalized in any society. 24,25 Consistent with previous studies, 26,27 statistical associations were found between gender and impact on quality of life, with the girls presenting 2.54 times more chances of having an impact than boys. Girls, usually, are more sensitive to the perception of their own appearance than boys, 26,28 present more attention, perception and appreciation of with own oral health.…”
Section: Discussionsupporting
confidence: 86%
“…Adolescent psychosocial behavior may be associated with dissatisfaction with dental appearance. 17,20 Insights about their attractiveness, especially concerning the dentofacial area, associated with the concomitant psychosocial impact play an essential role in adolescence. Better interpersonal relationships and thus greater self-confidence are a direct result of positive social interactions.…”
Section: Discussionmentioning
confidence: 99%
“…3,13,[17][18][19] Selfperceived dissatisfaction with dental esthetics has been reported to significantly influence the demand for orthodontic treatment. 7,10,14,20 Orthodontic treatment has an immediate, positive impact on the appearance and behavior of adolescents. 21 The esthetic and functional traits of a harmonious face may translate into higher intelligence and leadership skills, contributing to professional and personal growth.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 It has been well-documented that patients’ masticatory functions are negatively influenced by orofacial pain induced by tooth movement. 6 However, to date, no truly effective pain-relief treatment is available for tooth mechanical hyperalgesia induced by tooth movement. 4 This is partly attributed to poor understanding of its underlying mechanisms, justifying further in-depth mechanistic elucidation.…”
Section: Introductionmentioning
confidence: 99%